Calling Mogadishu: How Reminders of Anarchy Bias Survey Participation. Issue 2 (29th August 2018) - Denny, Elaine K.; Driscoll, Jesse
Abstract: How does the fear of anarchy affect telephone survey behaviors? A survey experiment administered to a sample of Mogadishu residents—validated with a natural experiment—is used to assess this question. Randomly assigned reminders of anarchic violence conditioned differential effects on survey participation depending on subjects' background level of security and welfare. Vulnerable subjects were more likely than non-vulnerable subjects to refuse to provide sensitive survey information after reminders of anarchy.